2001
DOI: 10.1046/j.1540-8167.2001.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Right Middle Pulmonary Vein in Patients with Paroxysmal Atrial Fibrillation

Abstract: RMPV was detected by MRA in >80% of paroxysmal AF patients. Ectopy from RMPV can initiate AF, and radiofrequency ablation of RMPV foci is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 3 publications
3
61
0
2
Order By: Relevance
“…771 A detailed understanding of this anatomy is essential for a safe and effective AF ablation procedure. 772 There is a significant inter- and intrapatient variability in the number, size, and bifurcation of the PVs 67,773, 774,775,776,777,778 (Figure 2). Common variations include supernumerary right PVs (18%–29%) and common trunk (>30%), mainly located on the left side and right middle or right top PV.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…771 A detailed understanding of this anatomy is essential for a safe and effective AF ablation procedure. 772 There is a significant inter- and intrapatient variability in the number, size, and bifurcation of the PVs 67,773, 774,775,776,777,778 (Figure 2). Common variations include supernumerary right PVs (18%–29%) and common trunk (>30%), mainly located on the left side and right middle or right top PV.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…[16] This arrhythmia is a cause of significant morbidity and mortality, with the highest risk being sudden cardiac death through heart failure. [6] The ectopic beats arising from the anomalous veins can give rise to thrombo-emboli and embolic stroke. Furthermore, atrial fibrillation has been shown to result in atrial remodeling by impacting atrial size.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The major sources of these ectopic beats appear to be the myocardial sleeves of the distal pulmonary veins which are simple extensions of the left atrial myocardium over the outer surface of pulmonary veins. [7,8] This is the reason why they became a target of interventional cardiology procedures such as catheter radiofrequency pulmonary vein isolation.…”
Section: Introductionmentioning
confidence: 99%
“…The return of regularly atrial function can be evaluated using cardio images. [1][2][3][4][5][6] The evaluation of atrial function is to determine the outcome of atrial ablation. [2] Therefore, to assess the outcome of atrial ablation non-invasively is to determine the change of volume at the diastolic phase and the systolic phase of left atrium.…”
Section: Introductionmentioning
confidence: 99%